Platelet-Mediated Mesenchymal Stem Cells Homing to the Lung Reduces Monocrotaline-Induced Rat Pulmonary Hypertension - Lei Jiang; Xing Hui Song; Pu Liu; Chun Lai Zeng; Zhang Sen Huang; Lin Jing Zhu; Yang Zi Jiang; Hong Wei Ouyang; Hu Hu (Cell Transplantation, 2012)
Bone marrow mesenchymal stem cell (BM-MSC) transplantation has been suggested to be a promising method for the treatment of pulmonary arterial hypertension (PAH), a fatal disease currently without effective preventive/therapeutic strategies. However, the detailed mechanisms underlying BM-MSC therapy are largely unknown. We designed the present study to test the hypothesis that circulating platelets facilitate BM-MSC homing to the lung vasculature in a rat model of PAH induced by monocrotalin (MCT). A single subcutaneous administration of MCT induced a marked rise in right ventricular systolic pressure (RVSP) and the weight ratio of right to left ventricle plus septum (RV/LV+S) 3 weeks after injection. The injection of MSCs via tail vein 3 days after MCT significantly reduced the increase of RVSP and RV/LV+S. The fluorescence-labeled MSCs injected into the PAH rat circulation were found mostly distributed in the lungs, particularly on the pulmonary vascular wall, whereas cell homing was abolished by an anti-P-selectin antibody and the GPIIb/IIIa inhibitor tirofiban. Furthermore, using an in vitro flow chamber, we demonstrated that MSC adhesion to the major extracellular matrix collagen was facilitated by platelets and their P-selectin and GPIIb/IIIa. Therefore, the current study suggested that platelet-mediated MSC homing prevented the aggravation of MCT-induced rat PAH, via P-selectin and GPIIb/IIIa-mediated mechanisms.